Rifampicin attenuates rotenone-treated microglia inflammation via improving lysosomal function. (March 2020) - Liang, Yanran; Zheng, Dezhi; Peng, Sudan; Lin, Danyu; Jing, Xiuna; Zeng, Zhifen; Chen, Ying; Huang, Kaixun; Xie, Yingyu; Zhou, Tianen; Tao, Enxiang
Abstract: Mounting evidence suggests that lysosome dysfunction promotes the progression of several neurodegenerative diseases via hampering autophagy flux. While regulation of autophagy in microglia may affect chronic inflammation involved in Parkinson's disease (PD). Our previous studies have reported rifampicin inhibits rotenone-induced microglia inflammation by enhancing autophagy, however the precise mechanism remains unclear. Human microglia (HM) cells were pretreated with 100 μM rifampicin for 2 h followed by exposure to 0.1 μM rotenone. We found that rifampicin pretreatment suppressed the gene expression of IL-1β and IL-6 via inhibiting activation of JNK after rotenone induction, but the anti-inflammatory effect of rifampicin was reversed by chloroquine. Moreover, rifampicin pretreatment not only improved the ratio of LC3-II/LC3-I in rotenone-treated cells, but also increased autolysosomes and decreased autophagosomes in RFP-GFP-LC3B transfected HM cells exposed to rotenone, thus indicating rifampicin improves autophagy flux in rotenone-treated HM cells. Finally, we verified rifampicin pretreatment enhanced ATP6V0A1 expression when compared to that exposed to rotenone alone. ATP6V0A1 knockdown inhibited the effect of rifampicin on maintaining lysosome acidification and autophagosome-lysosome fusion in rotenone-treated microglia. Taken together, our results indicated that rifampicin attenuates rotenone-induced microglia inflammation partially via elevating ATP6V0A1. Modulation of lysosomal function by rifampicin may be a novel therapeutic strategy for PD. Highlights: Autophagy inhibitor attenuated rifampicin's anti-inflammatory effect. Rifampicin improved autophagy flux in rotenone-treated microglia. Rifampicin enhanced expression of ATP6V0A1 in rotenone-treated microglia. Rifampicin improved lysosomal function by increasing ATP6V0A1 expression.